Warm season precipitation signal in [delta]2H values of wood lignin methoxyl groups from high elevation larch trees in Switzerland - Riechelmann, Dana; Greule, Markus; Anhäuser, Tobias; Keppler, Frank (Rapid communications in mass spectrometry, 2017)
Rationale: In this study, we tested stable hydrogen isotope ratios of wood lignin methoxyl groups (δ2Hmethoxyl values) as a palaeoclimate proxy in dendrochronology. This is a quite new method in the field of dendrochronology and the sample preparation is much simpler than the methods used before to measure δ2H values from wood. Methods: We measured δ2Hmethoxyl values in high elevation larch trees (Larix decidua Mill.) from Simplon Valley (southern Switzerland). Thirty-seven larch trees were sampled and five individuals analysed for their δ2Hmethoxyl values at annual (1971-2009) and pentadal resolution (1746-2009). The δ2Hmethoxyl values were measured as CH3I released upon treatment of the dried wood samples with hydroiodic acid. 10-90 μL from the head-space were injected into the gas chromatography/high-temperature conversion/isotope ratio mass spectrometry (GC/HTC-IRMS) system. Results: Testing the climate response of the δ2Hmethoxyl values, the annually resolved series show a positive correlation of r = 0.60 with June/July precipitation. The pentadally resolved δ2Hmethoxyl series do not show any significant correlation to climate parameters. Conclusions: Increased precipitation during June and July, which are on average warm and relatively dry months, results in higher δ2H values of the xylem water and, therefore, higher δ2H values in the lignin methoxyl groups. Therefore, we suggest that δ2Hmethoxyl values of high elevation larch trees might serve as a summer precipitation proxy.